2019
DOI: 10.3389/fneur.2019.01086
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Presentation of Anti-NMDA Receptor Encephalitis

Abstract: Background: Anti-N-methyl D-aspartate (NMDA) receptor encephalitis is an autoimmune condition characterized by neuropsychiatric symptoms, including epileptic seizures, movement disorders, autonomic instability, disturbances of consciousness, paranoia, delusions, and catatonia. Ovarian teratomas and viral infections, typically Herpes simplex viruses, have previously been demonstrated to precipitate anti-NMDA receptor encephalitis, but in many cases, the trigger remains unclear. The detection of anti-NMDA recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
0
31
0
3
Order By: Relevance
“…Initially, these Abs were only tested in the CSF, as CSF testing was considered more sensitive for the detection of anti-NMDAR encephalitis 45 . Our own observations revealed that anti-NMDAR encephalitis can probably also occur in patients with isolated positive serum results 38 , so serum analyses were introduced later, in addition to CSF analysis. The retrospective approach of the study also meant that confirmatory test results for the positive Ab findings from other investigators or with other methods or in other laboratories were not routinely performed.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, these Abs were only tested in the CSF, as CSF testing was considered more sensitive for the detection of anti-NMDAR encephalitis 45 . Our own observations revealed that anti-NMDAR encephalitis can probably also occur in patients with isolated positive serum results 38 , so serum analyses were introduced later, in addition to CSF analysis. The retrospective approach of the study also meant that confirmatory test results for the positive Ab findings from other investigators or with other methods or in other laboratories were not routinely performed.…”
Section: Discussionmentioning
confidence: 99%
“…Five patients developed an initial encephalitis with isolated [14,15,18,22,52,70] psychotic symptoms (0.9%), and 18 patients (3.2%) had isolated psychiatric symptoms during a relapse [44]. In the meantime, cases with isolated anti-NMDA-R Ab detection in the serum and typical [ 18 F]fluorodeoxyglucose positron emission tomography (FDG-PET) alterations were published [28]. In a case collection of 46 classic psychiatric Hashimoto encephalopathy cases, 12 patients suffered from acute psychosis (26.1%), and one patient met the criteria for schizophrenia (2.2%) [59].…”
Section: Predominant and Isolated Autoimmune Psychosismentioning
confidence: 99%
“…2 Red flags that should lead to antibody diagnostics (according to [2,5,22,36,53,55,61,67,74,76,77,85]). EEG electroencephalography, MRI magnetic resonance imaging All serum-Ab findings should be interpreted in the context of extended history data, the clinical syndrome, and the examination findings (especially including CSF Ab testing; [51,82,85] Compared to MRI, FDG-PET possibly has higher sensitivity for inflammatory changes ( [5,28,35]; Fig. 3).…”
Section: Indication For Antibody Analysesmentioning
confidence: 99%
“…The long untreated course may have enhanced the ongoing dysexecutive syndrome, as it is well known that late treatment is associated with poorer prognosis (4,6). A full remission can also be achieved in patients with a short course of disease (19). In the present patient, the symptomatic psychiatric treatment with low-dose, atypical neuroleptics and psychotherapy was also started late.…”
Section: Limitationsmentioning
confidence: 66%